The Chosen Peoples of the 11th and 21st Centuries (Relegere: Studies in Religion and Reception, 2012)
The idea of a people’s election by God is a narrative that attempts to efface contestation over the past, erasing history by constructing new memory. This paper will examine how this functions by comparing two Christian narratives of election. The Franks who participated in the First Crusade (1095-99) thought themselves to be God's new chosen people, who were in the process of reclaiming his favor. Similarly, a streak in contemporary evangelical (Judeo-)Christianity thinks itself at a point in that narrative just before the crusaders, with God showing his anger at his new chosen people (Americans). By understanding this process of narrativization, we understand that the idea of election suggests a course of action, in that it creates a hermeneutic seal around the "insiders," flattens differences among "outsiders," and requires the chosen people to fight back against the agents of God’s wrath.